Loss of CD98HC phosphorylation by ATM impairs antiporter trafficking and drives glutamate toxicity in Ataxia telangiectasia - July Carolina Romero; Sonal S. Tonapi; Manish Parihar; Eva Loranc; Henry E. Miller; Liesl A. Lawrence; Nicklas Bassani; Daniel G. Robledo; Lin Cao; Jia Nie; Kairi Kanda; Aiola Stoja; et al. (Nature Communications)
Abstract Ataxia-telangiectasia is a rare genetic disorder characterized by neurological defects, immunodeficiency, cancer predisposition, radiosensitivity, decreased blood vessel integrity, and diabetes. ATM, the protein mutated in Ataxia-telangiectasia, responds to DNA damage and oxidative stress, but its functional relationship to the progressive clinical manifestation of this disorder is not understood. CD98HC chaperones cystine/glutamate and cationic/neutral amino acid antiporters to the cell membrane, and CD98HC phosphorylation by ATM accelerates membrane localization to acutely increase amino acid transport. Loss of ATM impacts tissues reliant on heterodimeric amino acid transporters relevant to Ataxia-telangiectasia phenotypes, such as endothelial cells (telangiectasia) and pancreatic α-cells (fatty liver and diabetes), with toxic glutamate accumulation. Bypassing the antiporters restores intracellular metabolic balance in ATM-deficient cells and mouse models. These findings provide insight into the long-known benefits of N-acetyl cysteine in Ataxia-telangiectasia cells beyond oxidative stress through removing glutamate excess by producing glutathione.